Estresse ocupacional em mototaxistas de uma cidade do interior da Paraíba. - Figueiredo, José Aurélio de Oliveira (2017)
Occupational stress is nowadays a recognized problem worldwide; Behavioral changes in society, inadequate lifestyle, work processes, advances professional exhaustion and provide increased occupational stress. The motoboys have as work environment the street, one place of several factors of risks for the physical and mental health. Objective: To cosntrue the factors associated with occupational stressors in motoboys. Methods: A cross - sectional epidemiological study was carried out with 95 motoboys from the city of Cajazeiras - PB. Data collection was performed through blood gathering and questionnaire completion, from February to May 2016. The data levy instrument contained questions on sociodemographic, lifestyle, health, labor and occupational stress data, assessed Through demand, control and social support at work Variables were described by means of absolute and relative frequencies, measures of central tendency (average) and dispersion (standard deviation). To test the normality of the quantitative variables, the Kolmogorov-Sminov test was performed. The Kruskal-Wallis or Mann Whitney tests were used to compare the means of the non-parametric variables and to the parametric variables ANOVA or t-student. The correlation test used was Sperman or Pearson, the hypothesis tests of proportion were Chi-square or Fisher's Exact. In all tests, the value of ""p"" less than 0.05 was considered significant. Results: All motoboys were males, average age 37.1 ± 8.0 years. The working time as mototaxistas was of 9.4 + 4.6 years, being the daily monthly day of 5.3 + 2.2 hours / day. Almost half of those interviewed work at night (up to 24 hours). 50.5% do not take breaks during working hours, only limiting themselves to meal intervals. 66.3% have moderate necessity for recovery after work, however, 67.4% have a low labor capacity index. It was found that 72.6% had symptoms of insomnia. The majority (51.6%) had a high labor demand, followed by high control (54.7%) and low social support at work (61.1%). The highest proportion of motorcycle racers was classified as having low wear (28.4%), followed by active work (26.3%). There was no difference in the variables of lifestyle, health and work according to the occupational stressors and the demand-control model. We verified a higher proportion of motoboys with low labor demand, as well as passive work with higher glycemic levels. There was a positive correlation between labor demand and LDL (p <0.05). Conclusion: There was no association among the variables etudes and the occupational stressors. The mototaxistas presented high demand for work and social support, but on the other hand, high control at work.